Preferential Repair of the Transcribed DNA Strand in Plants - Fidantsef, Ana L.; Britt, Anne B. (Frontiers in Plant Science, 2012)
UV-induced pyrimidine dimers block the progression of both DNA and RNA polymerases. In order to reduce the disruptive effect of these lesions on gene expression, bacteria, yeasts, and animals preferentially repair the transcribed strand of actively expressed genes, essentially employing the stalled polymerase as a detector for bulky lesions. It has been assumed, but not demonstrated, that this prioritization of repair also occurs in plants. Here we demonstrate that in the constitutively expressed gene encoding the RNA polymerase II large subunit cyclobutane pyrimidine dimers are removed from the transcribed strand more rapidly than from the nontranscribed strand.